Oral Health Status among Postmenopausal Women Attending Tertiary Hospital of Bharatpur, Nepal - Bhattarai, Rosina; Ghosh, Snehashish; Yadav, Deependra Kumar; Neupane, Ajay (Nepal Journal of Health Sciences, 2024)
Introduction: Menopause is a biological process occurring in middle aged women causing changes in the level of circulating hormones. Changes in the oral flora, oral mucosa and decrease in bone mineral density leads to many menopauses related oral findings. Objective: This study was conducted with the objective to assess the oral health status of postmenopausal women visiting tertiary health care centre in Bharatpur, Chitwan. Methods: Analytical cross-sectional study was conducted among 224 postmenopausal women attending dental OPD in a tertiary health care centre. Comprehensive oral examination was done where CPITN index was used to record periodontal health and DMFT index was used to record caries experience of the patient. Data entry was done in Microsoft Excel and statistical analysis was done using SPSS version 20. Results: Total 224 patients were examined with age range of 45 to 78 years and the mean age of 56.71 years. 113 study participants comprising 50.4%, showed supra or subgingival calculus followed by gingival bleeding in 54 (24.1%). Mean decayed score among study participants was found to be 2.71±2.85, mean missing score was found to be 4.29±7.83. Conclusion: Mean score for missing teeth suggestive of sequel of dental caries and periodontitis was found higher among the post-menopausal women followed by mean decayed score. Dental caries score was high probably due to dryness of mouth and other predisposing factors.